Implementasi Prinsip Amar Makruf Nahi Munkar sebagai Etika Politik - Arif, Dirga (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research describes the implementation of the Amar Ma'ruf Nahi Munkar principles as Islamic political ethics. Amar Ma'ruf Nahi Munkar is an effort to realize the common good, not just for one particular group or group. This research aims to determine the extent to which the Amar Ma'ruf Nahi Munkar principles are implemented as Islamic political ethics. Islam teaches its people to have good ethics. One of them uses Amar Ma'ruf Nahi Munkar as a guide. This research applies qualitative research methods with a descriptive approach. The results of this research are one of the main foundations of Islamic teachings that Allah commanded fellow Muslims to implement. To create a strong and civilized Muslim society, principles are needed that unite every individual in doing good and avoiding evil to achieve the common good. In this case, Amar Makruf Nahi Munkar is a principle offered by Islam in building a strong and civilized society.